2017
DOI: 10.1021/acs.molpharmaceut.7b00862
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Artemether-Loaded Poly(lactic-co-glycolic) Acid Microparticles Fabricated by Coaxial Electrospray: Validation of Enhanced Encapsulation Efficiency and Bioavailability

Abstract: Artemether is one of the most effective drugs for the treatment of chloroquine-resistant and Plasmodium falciparum strains of malaria. However, its therapeutic potency is hindered by its poor bioavailability. To overcome this limitation, we have encapsulated artemether in poly(lactic-co-glycolic) acid (PLGA) core-shell microparticles (MPs) using the coaxial electrospray method. With optimized process parameters including liquid flow rates and applied electric voltages, experiments are systematically carried ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…Moreover, ES settings can be varied by changing the collector. There are several types of collectors used to obtain particles, such as aluminum plates [31][32][33], stainless steel plates [34,35], steel plates covered with foil [15,32] and the receiver solution [28,[36][37][38][39], which are all demonstrated in Figure 2a-d. Moreover, previous studies have demonstrated the use of alcohol solutions, buffers and surfactants as the MP receptor solution [28,[36][37][38][39].…”
Section: Types Of Configurationmentioning
confidence: 99%
“…Moreover, ES settings can be varied by changing the collector. There are several types of collectors used to obtain particles, such as aluminum plates [31][32][33], stainless steel plates [34,35], steel plates covered with foil [15,32] and the receiver solution [28,[36][37][38][39], which are all demonstrated in Figure 2a-d. Moreover, previous studies have demonstrated the use of alcohol solutions, buffers and surfactants as the MP receptor solution [28,[36][37][38][39].…”
Section: Types Of Configurationmentioning
confidence: 99%
“…Recently, we succeeded in preparing artemether-loaded and curcumin-loaded core-shell-structured PLGA MPs using CEHDA process for different applications in our lab [23,34]. However, in the present study, we have developed CEHDA technology for scalable production of PTX-laden SLMPs (PTX-SLMPs) with core-shell structure in a single-step process.…”
Section: Introductionmentioning
confidence: 92%
“…The effects of liquid properties on the electrospraying process. [10], [11] Reprinted with permission. Copyright (2019) American Chemical Society.…”
Section: Pharmaceutical Applicationsmentioning
confidence: 99%